2022
DOI: 10.1007/s00262-022-03197-2
|View full text |Cite|
|
Sign up to set email alerts
|

Tcf-1 protects anti-tumor TCR-engineered CD8+ T-cells from GzmB mediated self-destruction

Abstract: Background T-cell longevity is undermined by antigen-driven differentiation programs that render cells prone to attrition through several mechanisms. CD8 + T cells that express the Tcf-1 transcription factor have undergone limited differentiation and exhibit stem-cell-like replenishment functions that facilitate persistence. We engineered human CD8 + T cells to constitutively express Tcf-1 and a TCR specific for the NY-ESO-1 cancer-associated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…6D ). In line with GSEA results, chronic stimulation led to an increase in the proportion of CD8 + TET2-TRAC-CAR19 cells expressing the progenitor-associated TF TCF1 ( 60 ) and a decrease in the proportion of cells expressing the terminal differentiation-associated effector molecule granzyme B ( 61 ) compared to TRAC-CAR19 control cells ( Fig. 6E, fig.…”
Section: Resultssupporting
confidence: 83%
“…6D ). In line with GSEA results, chronic stimulation led to an increase in the proportion of CD8 + TET2-TRAC-CAR19 cells expressing the progenitor-associated TF TCF1 ( 60 ) and a decrease in the proportion of cells expressing the terminal differentiation-associated effector molecule granzyme B ( 61 ) compared to TRAC-CAR19 control cells ( Fig. 6E, fig.…”
Section: Resultssupporting
confidence: 83%
“…Of note, although the majority of the FR-B 2/15 T cells that accumulated in the peritoneal TME were CD8+TALs, we also noted a modest increase in the frequency of FR-B 2/15 CD4+TALs compared with FR-B 2/7 CD4+TALs, suggesting IL-2/IL-15 preconditioning can improve the accumulation/persistence of both FR-B T cell subsets. While IL-2/IL-15 preconditioning produced stem-like FR-B T cells with a predominantly TCF-1+CD39–CD69– phenotype and improved persistence, we also recently reported on engineering T cells to stably express TCF-1 to enhance T-cell persistence 37 and this approach could be incorporated when generating BiTE-T cells. Importantly, unlike conventional ACT approaches (eg, engineering tumor reactive CAR-T or TCR-T cells) where therapeutic failure can stem from limited tumor infiltration following T-cell infusion, the capacity of BiTE-T cells to mediate tumor attack from remote location(s) outside of solid tumors suggests strategies for generating durable responses may differ among these approaches.…”
Section: Discussionmentioning
confidence: 88%
“…As a serine protease, GZMB is expressed by cytotoxic T lymphocytes and NK cells. Many studies have indicated a signi cant upregulation of GZMB in RA, and its expression is associated with the occurrence and progression of RA [43] . It is worth mentioning that GZMB has certain functions in tumor immune in ltration such as skin cutaneous melanoma and colorectal cancer [44,45] .…”
Section: Discussionmentioning
confidence: 99%